FUNCTIONAL EVALUATION OF PATIENTS WITH TRANSFEMORAL AMPUTATION PROSTHESES (Fiep Bulletin - online, 2014)
Introduction: Amputation is considered traumatic or surgical removal of a limb. The aim of this study was to analyze the level of functional independence in unilateral transfemoral amputees fitted with hearing aids and the factors that influence the region. Methodology: a quantitative cross-sectional primary source that examined the functional independence in patients with unilateral transfemoral amputees at prothetizades through the questionnaire functional measure for amputees (FMA), in order to evaluate the components of the prosthesis and check the difference polycentric prosthetic knee for young and knee prosthetic monoeixo with lock for the elderly, associated with the same functional independence, mobility, use of prosthesis and identify factors that may be influencing the results. Results: After the questionnaire it was found that the responses were less satisfactory individuals aged 60 to 78 years, with shorter prosthesis use this as 8, 9 and 10 months, and these have knee monoeixo lockable. Conclusion: In this study it can be concluded that the prosthetic knee influence on functional independence as it has different indications for the population that is composed of young and old. In relation to age and time of use of the prosthesis (hours / day) concludes that there are determinants for the individual to adopt their functional independence.
Keywords: transfemoral amputees; functional assessment; prosthetic components